Integrative Multi-Omics Analysis of Identified NUF2 as a Candidate Oncogene Correlates With Poor Prognosis and Immune Infiltration in Non-Small Cell Lung Cancer - Chen, Mengqing; Li, Shangkun; Liang, Yuling; Zhang, Yue; Luo, Dan; Wang, Wenjun (Frontiers in Oncology, 2021)
Background: Lung cancer is one of the most common malignant tumors and the leading causes of cancer-related deaths worldwide. As a component of the nuclear division cycle 80 complex, NUF2 is a part of the conserved protein complex related to the centromere. Although the high expression of NUF2 has been reported in many different types of human cancers, the multi-omics analysis in non-small cell lung cancer(NSCLC) of NUF2 remains to be elucidated. Methods: In this analysis, NUF2 expression difference analysis in non-small cell lung cancer were evaluated by Oncomine, TIMER, GEO and TCGA database. And the prognosis analysis of NUF2 based on Kaplan-Meier was performed. R language was used to analyze the differential expression genes, functional annotation and protein-protein interaction(PPI). GSEA analysis of differential expression genes were also carried out. Mechanism analysis about exploring the characteristic of NUF2, multi-omics and correlation analysis were carried out using UALCAN, cBioportal, GEPIA, TIMER and TISIDB. Results: The expression of NUF2 in NSCLC(lung adenocarcinoma(LUAD) and squamous lung cancer(LUSC)) was significantly higher than that in normal tissues. The analysis of UALCAN database samples proved that NUF2 expression was connected with stage and smoking habits. Meanwhile, the overall survival curve also validated that high expression of NUF2 indicated poorer prognosis in NSCLC. GO, KEGG, GSEA, subcellular location from COMPARTMENTS indicated that NUF2 may regulate the cell cycle. Correlation analysis also showed NUF2 was mainly positively associated with cell cycle and tumor-related genes. NUF2 altered group had a poorer prognosis than unaltered group in NSCLC. Immune infiltration analysis showed the NUF2 expression have negatively correlation with immune cells and immune subtypes in LUAD and LUSC. Furthermore, reverse transcription polymerase chain reaction was used to validated the expression difference of NUF2 in LUAD and LUSC. Conclusion: Our findings elucidated NUF2 may play an important role in cell cycle, and significantly associated with tumor-related gene, we consider that NUF2 may be a prognostic biomarkers in NSCLC.